Concentration, functional inequalities and isoperimetry : International Workshop on Concentration, Functional Inequalities and Isoperimetry, October 29-November 1, 2009, Florida Atlantic University, Boca Raton, Florida - International Workshop on Concentration, Functional Inequalities and Isoperimetry; Houdré, Christian; Ledoux, Michel; Milman, Emanuel; Milman, Mario (Contemporary mathematics, 2011)
The volume contains the proceedings of the international workshop on Concentration, Functional Inequalities and Isoperimetry, held at Florida Atlantic University in Boca Raton, Florida, from October 29-November 1, 2009. The interactions between concentration, isoperimetry and functional inequalities have led to many significant advances in functional analysis and probability theory. Important progress has also taken place in combinatorics, geometry, harmonic analysis and mathematical physics, to name but a few fields, with recent new applications in random matrices and information theory. This book should appeal to graduate students and researchers interested in the fascinating interplay between analysis, probability, and geometry.